Surface modification using the biomimetic method in alumina-zirconia porous ceramics obtained by the replica method - Silva, Andre D. R.; Rigoli, Willian R.; Osiro, Denise; Mello, Daphne C. R. [UNESP]; Vasconcellos, Luana M. R. [UNESP]; Lobo, Anderson O.; Pallone, Eliria M. J. A. (Wiley-Blackwell, 2018)
The modification of biomaterials approved by the Food and Drug Administration could be an alternative to reduce the period of use in humans. Porous bioceramics are widely used as support structures for bone formation and repair. This composite has essential characteristics for an implant, including good mechanical properties, high chemical stability, biocompatibility and adequate aesthetic appearance. Here, three-dimensional porous scaffolds of Al2O3 containing 5% by volume of ZrO2 were produced by the replica method. These scaffolds had their surfaces chemically treated with phosphoric acid and were coated with calcium phosphate using the biomimetic method simulated body fluid (SBF, 5x) for 14 days. The scaffolds, before and after biomimetic coating, were characterized mechanically, morphologically and structurally by axial compression tests, scanning electron microscopy, microtomography, apparent porosity, X-ray diffractometry, near-infrared spectroscopy, inductively coupled plasma optical emission spectroscopy, energy dispersive X-ray spectroscopy and reactivity. The in vitro cell viability and formation of mineralization nodules were used to identify the potential for bone regeneration. The produced scaffols after immersion in SBF were able to induce the nodules formation. These characteristics are advantaged by the formation of different phases of calcium phosphates on the material surface in a reduced incubation period. (c) 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2615-2624, 2018.
Keywords: replica method; scaffolds; calcium phosphate; biomimetic coating; alumina-zirconia